The entrepreneurial ecosystem in the face of the pandemic: how to get through a crisis and survive it - Bonomo-Odizzio, Adriana; Krauss-Delorme, Catherine; Correa-Garcia, Patricia (RAN - Revista Academia & Negocios, 2023)
Purpose: To identify and analyze the institutional factors of the Uruguayan entrepreneurial ecosystem, its capacity to respond to crises, and to provide a methodology for dealing with them. Design/Methodology: Descriptive and explanatory methodology, with a mixed approach, semi-directed interviews with entrepreneurs, a non-probabilistic survey, and a workshop for exchange with the institutions sponsoring ventures. Results: A self-diagnosis software and a manual of good practices were developed based on detecting the main problems encountered by public and private organizations that support entrepreneurs during the pandemic. Originality/value: It has both practical and social implications. It seeks to strengthen the entrepreneurial ecosystem, provide self-diagnostic tools to improve its performance during a crisis, and develop recommended strategies through a manual of good practices.